Enhancing Generative Adversarial Networks with Structural Similarity Index and Fuzzy Logic-Based Loss Functions (SSIM_T) - Farhadi Nia, Bahram; Ahangari, Mohammad Reza; Ebrahimi, Seyyed Javad (Optimality, 2025)
Generative Adversarial Networks (GANs) have emerged as a powerful paradigm for unsupervised learning and generative modeling, enabling the synthesis of high-quality, realistic data across various domains. However, GAN training is notoriously challenging, often plagued by issues such as mode collapse, instability, and a lack of perceptual fidelity in generated samples. Traditional loss functions, primarily based on pixel-wise comparisons, fail to capture the complex structural and perceptual attributes of images, hindering the generation of visually compelling outputs. This paper introduces a novel loss function for GANs that integrates the Structural Similarity Index (SSIM) with fuzzy logic t-norms (SSIM_T). By leveraging SSIM_T, the proposed approach enhances perceptual similarity between generated and real images while harnessing the power of fuzzy logic to model the inherent uncertainty and nuanced relationships within image data. Theoretical analysis and extensive experiments demonstrate that SSIM_T mitigates mode collapse, stabilizes training dynamics, and produces visually coherent outputs, surpassing existing loss functions, including those based on Sugeno complements. This work bridges advancements in structural similarity metrics and fuzzy logic, offering a robust and perceptually driven framework for image-processing applications and beyond.